Cultural heritage and environmental ethical values in governance models: Conflicts between recreational fisheries and other maritime activities in Mediterranean marine protected areas - Gómez, Sílvia; Carreño, Arnau; Lloret, Josep (Marine policy, 2021)
The seas as the next economic frontier have led to conflicts at the intersection of resource conservation and exploitation; a space where cultural values and social practices overlap. Underpinned by a literature review, surveys and personal interviews, this study identifies the main policy, socio-economic, environmental and cultural drivers of conflicts arising from the coexistence of recreational fishing -a major maritime activity in Mediterranean marine protected areas- and other maritime users. Results show that the constant paradoxes arising from the conflict stem from different concepts of heritage, appropriation of resources and preservation. Recreational fishing lacks a common definition and governance institution, but nevertheless regards itself as a fishing community and has behavioural traits which challenge other maritime activities, particularly small-scale fishing. This study highlights the importance of fostering socio-ecological relational values, which must necessarily be evaluated through the lens of environmental ethics, and contends that this is almost as relevant as the governance system. Given the divergent values of the different stakeholders and the high degree of scientific uncertainty found, we conclude that the main challenge in attaining a solid governance of multiple recreational and professional activities in marine reserves is to adopt a "middle ground" approach that combines top-down and bottom-up governance approaches. •Drivers of conflict in Mediterranean marine protected areas are identified•A common definition of recreational fisheries and licence systems is needed•Other maritime activities are challenged by recreational fishing traits•The governance system needs to foster ethical and moral socioecological values•Governance plans should adopt a middle-ground approach